THE ABUNDANCE OF RECENT FORAMINIFERA IN SURFACE SEDIMENT OF AMBON BAY - Suhartati M. Natsir (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2010)
Foraminifera are generally live in sea water with various sizes. These organisms consist of planktonic and benthic foraminifera. Geological activity on plutonic and volcanic with vomiting magma is transpiring on, and then affects sedimentation and foraminiferal abundance of Ambon Bay. The study was determined to study the abundance and distribution of foraminifera based on the sediment characteristic of Ambon Bay. Sample collected in 2007 of Ambon Bay showed that only 29 samples of 50 samples containing foraminifera. The collected sediments have 86 species of foraminifera, consisting 61 species of benthic foraminifera and 25 species of planktonic foraminifera. The dominant benthic foraminifera in the surface sediment of Ambon bay were Amphistegina lessonii, Ammoniabeccarii,Elphidium craticulatum,Operculina ammonoides and Quinqueloculina parkery. The planktonic foraminifera that were frequently collected from the bay were Globorotalia tumida, Globoquadrina pseudofoliata, Globigerinoides pseudofoliata, Globigerinoides cyclostomus dan Pulleniatina finalis. Generally, the species dwelled as abundant on substrate sand, whereas the areas within substrate mud have no foraminifera lie on them. Keywords: Foraminifera, Abundance, Sediment, Ambon Bay